L’ecosistema digitale Artence basato su blockchain per la valorizzazione e scambio di Non Fungible Tokens (NFT) - Archeomatica, Redazione (Archeomatica, 2023)
Artence is an international project as it aims to bring together in a single environment resources from all over the world of contemporary artists (digital or traditional), collectors, art galleries, foundations, public museums and private museums. A real collector capable of attracting content from all over the world with the guarantee of uniqueness and authenticity that each NFT is specially created and certified on the Blockchain. Furthermore, Artence offers a series of related services to differentiate its offer from similar competitors, and brings together works of art of different belonging between painting, photography, music and audiovisual.